POTENTIAL DIFFICULTIES IN LEARNING LISTENING - Rashidova, Nodira (Журнал иностранных языков и лингвистики, 2021)
As it is known listening is one of the important parts of learning foreign language. Moreover two more problems faced by university students were limited vocabulary and paralinguistic issues. Students sometimes encounter unfamiliar words which caused them to stop and think about the meaning of those words and they missed the next part of the speech. In the same way, paralinguistic features such as the accent, noise, rate of delivery, pronunciation, and intonation caused students difficulties while doing listening exercises. This article defines difficulties of doing listening tasks and the ways of solving them.